2022
DOI: 10.1038/s41598-022-09860-z
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of metribuzin pesticide by Cucumber (Cucumis sativus) peels-zinc oxide nanoparticles composite

Abstract: Herein, a biosorbent was prepared from cucumber peels modified with ZnO nanoparticles (CPZiONp-composite) for the biosorption of metribuzin. Characterization of the composite was accomplished using FTIR, SEM, EDX, surface area pore size analyzer and pH of point of zero charge (pHpzc). Biosorption study was executed in batch concerning the impact of pH, composite dose, contact time, initial metribuzin concentration and temperature. The biosorption depends on pH and maximum biosorption was acquired at pH 3.0. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Based on the linear correlation (R2) data, the second-order kinetics experiments showed better linearity than that of the first-order kinetics. This result suggests that the sorption process operates via an electrostatic mechanism, where the MB dye and the functional groups on BCDs share charges 74 .…”
Section: Resultsmentioning
confidence: 94%
“…Based on the linear correlation (R2) data, the second-order kinetics experiments showed better linearity than that of the first-order kinetics. This result suggests that the sorption process operates via an electrostatic mechanism, where the MB dye and the functional groups on BCDs share charges 74 .…”
Section: Resultsmentioning
confidence: 94%
“…Brinkman et al (1980) and Fuscaldo et al (1999) demonstrated the potential utility of oats in estimating residues of atrazine and metribuzin in soil due to its high sensitivity to the inhibitory effects of these herbicides on seedling growth. Conversely, Simard et al (2017) and Haq et al (2022) highlighted the sensitivity of cucumber and mallow (molokhia) to the herbicide linuron. Moreover, several researchers (Chopra et al, 2015;Chen et al 2019;Jiang et al, 2022) have also suggested the use of wheat and barley in estimating pendimethalin residues.…”
Section: Pendimethalinmentioning
confidence: 99%
“…Various studies have been carried out to develop nanomaterial-based adsorbents for the removal of pesticides from water. MET and DIC pesticides removal from water has been examined by amino-functionalized Fe 3 O 4 nanoparticles, [12] magnetic switchgrass biochar(MSGB), [13] coal fly ash, [14] cucumber peel modified with ZnO nanoparticles, [15] dispersive-micro-solid phase extraction by dendrimer-modified MNPs, [16] and pyrene based organic polymer. [17] All reported adsorbents can adsorb pesticides but their specificity and selectivity for nitrogenous pesticides are not optimum.…”
Section: Introductionmentioning
confidence: 99%